Knowledge, attitude and practices regarding the use of personal protective equipment during COVID-19 pandemic among health care workers at a tertiary health care center - Badgujar, Jatin V.; Sharma, Gaurav M.; Relwani, Nisha R.; Rohondia, Omprakash S.; Patole, Tanvi D.; Puntambekar, Anjali S. (International Journal Of Community Medicine And Public Health, 2021)
Background: The aim of the present study was to assess the knowledge, attitude and practices (KAP) regarding the use of personal protective equipment (PPE) during COVID-19 pandemic among health care workers. Methods: A cross-sectional study was conducted among health care workers (HCW) including junior and senior resident doctors and nursing staff working at a tertiary health care center. A pre-designed, pre-validated, semi-structured questionnaire regarding the use of PPE was distributed online to eligible HCW and their responses were recorded electronically between 14 April 2020 and 20 April 2020. The survey questionnaire consisted of questions based on demographic and background characteristics along with KAP; knowledge (K1-K6), attitude (A1-A3) and practices (P1-P4). Results: A total of 423 out of 475 eligible participants successfully submitted their responses and were included in the present study which included junior resident doctors (55.70%), senior resident doctors (19.60%) and nursing staff (24.60%). The mean total knowledge score was 4.169±1.006 with an overall correct response rate of 75.8%. The result of one way ANOVA indicated that there is significant difference in the mean total knowledge score according to designation (F=6602, p<01) with improved knowledge score seen in HCW with higher designation. Majority of HCW had positive attitude and appropriate practices regarding the use of PPE. Conclusions: Optimal use of PPE is crucial to avoid transmission of infection in health care setting. Assessment of KAP of HCW regarding the use of PPE can help hospital authorities to introduce educational programs accordingly to gaps identified in the survey.